Remuneration system – selected aspects of measuring effectiveness - Malarski, Maciej (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The remuneration system is one of the most important components of motivation in enterprises. Properly built contributes to the proper activity of employees, aimed at achieving the goals of the enterprise, showing the right behaviors and attitudes. This chapter is an attempt to define how the effectiveness of the remuneration system can be measured, taking into account various measurement dimensions.